Bone remodeling at microscrew interface near extraction site in the beagle dog mandible-histologic and immunohistochemical analyses - WEI, Guangxi (Faculdade de Odontologia de Bauru da Universidade de São Paulo, 2013)
Extraction is often used as part of orthodontic therapy, and good control of anchorage is a key step after extraction. Although microscrews can be implanted close to the extraction site in order to achieve orthodontic support, the efficiency of bone remodeling at the implant-bone interface near the extraction region is dubious. OBJECTIVE: The purpose of this study was to investigate bone remodeling of the bone-microscrew interface near the tooth extraction site, in the absence of loading. MATERIAL AND METHODS: Third and fourth premolars were extracted from the mandibles of beagle dogs, followed by placement of test microscrews near the extraction sites. Control microscrews were placed further away from the extraction site. All samples were collected after 1, 3, 8, or 12 weeks of healing following extraction. The bone remodeling process at the interface was evaluated using histologic and immunohistochemical analyses. RESULTS: Initially, a large number of inflammatory cells were aggregated at the interface. The expression levels of core binding factor (Cbfa1), osteocalcin (OC) and transforming growth factor beta (TGF-β) were inconspicuous in both groups, whereas tumor necrosis factor alpha (TNF-α) was strongly expressed, especially in the test groups (P<0.05). Subsequently, the expression levels of Cbfa1, OC and TGF-β were found to increase significantly, and active osteogenesis was observed. CONCLUSIONS: During week 1, inflammatory reaction is a major concern at the bone-microscrew interface near the extraction site. However, with healing, the influence of extraction on the remodeling of bone surrounding the microscrews decreases, thus facilitating successful treatment.